Analisis Prosedur Pemberian Kredit Usaha Rakyat Pada BRI Palangka Raya Unit Yos Sudarso - Widayanti, Widayanti; Eko Riadi; Alexandro, Rinto; Dehen Erang; Putri, Windy Utami (FKIP, Universitas Palangka Raya, 2022)
People's Business Credit is one of the government programs that aims to help the Indonesian people who have small businesses to prosper the nation's economy which is carried out by certain banks, one of which is BRI. This study aims to analyze the procedures for granting public private loans as well as the supporting and inhibiting factors for distributing people's business loans at Bank BRI Palangka Raya Unit Yos Sudarso. In this study using qualitative analysis, qualitative analysis techniques are carried out by collecting, compiling and drawing conclusions about the procedure for granting People's Business Credit (KUR) at Bank BRI Palangka Raya unit Yos Sudarso. The techniques of data collection procedures in qualitative analysis are interviews, observation and documentation. Interviews were conducted with the Bank who understands the procedure for granting KUR and one of the customers of the BRI KUR Palangka Raya unit, Yos Sudarso. Based on the results of the research that has been carried out, it shows that the procedure for providing People's Business Credit (KUR) at Bank BRI Palangka Raya unit Yos Sudarso has been carried out quite well and in accordance with government regulations, namely the first stage of credit application, namely the process of collecting administrative data as the first requirement to apply KUR. The second stage is credit analysis, analyzing administrative files and making visits to prospective customers' places of business. The third stage is the credit decision, the head of the unit will provide the final result, namely the credit decision. The fourth stage is credit disbursement, which is filling out a credit agreement or credit agreement regarding the rights and obligations of the customer. The supporting factors for distributing people's business loans are data on business actors who received assistance from the president for MSMEs and data from the market office. The inhibiting factors for the distribution of people's business loans are business actors who do not and do not want to apply for loans and business actors who have businesses but have a bad loan history and some customers who apply for loans but do not own businesses.